PRINCIPLES OF CLASSIFICATION OF TOPONYMIC NAMES (Conferencea, 2022)
This article is devoted to one of the controversial issues in the field of modern linguistics - the classification of toponyms. There are various opinions of linguists about the classification of proper names, many of which are given in this article. The exact interpretation of the terms that denote the various names of objects in our universe is given